2014
DOI: 10.1037/a0037845
|View full text |Cite
|
Sign up to set email alerts
|

Coherence and content of conflict-based narratives: Associations to family risk and maladjustment.

Abstract: This study examined the role of structural and content characteristics of children's conflict-based narratives (coherence, positive and aggressive themes) in the association between early childhood family risk and children's internalizing and externalizing problems in a sample of 193 children (97 girls, 96 boys) aged 3 to 5 years (M = 3.85, SD = .48). Parents participated in an interview on family related risk factors; teachers and parents completed the Strengths and Difficulties Questionnaire; children comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 52 publications
3
23
3
Order By: Relevance
“…Our results do not correspond to findings of previous studies, which have shown negative associations between narrative coherence and children's symptoms (e.g., Muller et al, 2014;von Klitzing et al, 2000). However, Muller et al (2014) found asso ciations only with teacher reports on internalizing symptoms but not with parent reports. In another study by our research group, narrative coherence and internalizing symptoms (multi-informant report parent, teacher, and child) were also unrelated (Stadelmann, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results do not correspond to findings of previous studies, which have shown negative associations between narrative coherence and children's symptoms (e.g., Muller et al, 2014;von Klitzing et al, 2000). However, Muller et al (2014) found asso ciations only with teacher reports on internalizing symptoms but not with parent reports. In another study by our research group, narrative coherence and internalizing symptoms (multi-informant report parent, teacher, and child) were also unrelated (Stadelmann, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…These findings sup port the notion of attachment theory that children's representations develop over time within the parent-child relationship, and that the organization of experiences, as reflected in narrative coher ence, can be negatively affected by inadequate caregiving (Oppen heim & Waters, 1995). However, in other studies, family risk factors such as parental anxiety (Warren, Emde, & Sroufe, 2000), the mother's experience of domestic violence as an adult and as a child (Schechter et al, 2007), or an accumulated family risk (Muller et al, 2014) were not found to be significantly associated with children's narrative coherence. Some of the family risk fac tors assessed in these studies might be more distal or short-term stressors that affect not (yet) children's narrative coherence.…”
Section: Maternal Psychosocial Stress Internalizing Symptoms and Namentioning
confidence: 84%
“…Individuals who experience difficulty with narrating about personal experiences in a coherent manner show more internalizing as well as externalizing symptoms. More specifically, memory incoherence has been associated with depressive symptoms, behavioral problems, and PTSD (e.g., Foa et al, 1995 ; von Klitzing et al, 2000 ; von Klitzing et al, 2007 ; Müller et al, 2014 ; Stadelmann et al, 2015 ). Additionally, a pattern of incoherence has been observed in patients suffering from a borderline personality disorder, eating disorder, and obsessive-compulsive disorder ( Rasmussen et al, 2017 ).…”
Section: Memory Coherencementioning
confidence: 99%
“…As we discussed earlier, memory coherence enables creating meaning out of a negative or stressful event and regulating the related cognitions and emotions. As a result, it can be argued that memory coherence protects the individual from the damaging effects negative life experiences can have on well-being, making incoherent persons more vulnerable ( Müller et al, 2014 ; Stadelmann et al, 2015 ). However, there are still some outstanding questions and inconsistencies regarding the association between memory coherence and psychopathology, which we will discuss in more detail below.…”
Section: Memory Coherencementioning
confidence: 99%
“…Accordingly, the coherence of young adults’ autobiographical narratives of personally significant events has been found to be positively associated with psychological well-being, with the experience of purpose and meaning in life, and with maintaining positive relationships (Waters and Fivush, 2015), and negatively associated with depressive symptoms (Vanderveren et al., 2019). In children, higher coherence has also found to be associated with less internalizing and externalizing problems (von Klitzing et al., 2000; Müller et al., 2014). Moreover, some studies showed that high narrative coherence can buffer the negative impact of adverse life experiences and family risk factors (Müller et al., 2014; Stadelmann et al., 2015).…”
Section: Introductionmentioning
confidence: 99%